International corporate governance and regulation - John, Kose; Makhija, Anil K.; Ferris, Stephen P. (Bingley, U.K. : Emerald Publishing Limited, 2018)
Advances in Financial Economics volume 20 deals with International Corporate Governance, particularly the role played by boards of directors, internal organization design and governance mechanisms, franchise agreements, the effect of regulation and policy, the market for corporate control, and strategic alliances.
Prelims -- Climate policies with burden sharing: the economics of climate financing -- Board gender diversity and firm financial performance: a quantile regression analysis -- Are dividends an outcome of or a substitute for external corporate governance? international evidence based on product market competition -- International evidence on economic freedom, governance, and firm performance -- Should we trust fund managers? a close look at the Canadian mutual fund governance -- The influence of corporate governance mechanisms on the behavior of financial analysts of US firms: an empirical analysis -- Corporate governance that influences an investment intention in the ASEAN-Stars Thai Listed companies: a marketing application for brokerage firms -- Reconsidering the mandate of the audit committee: evidence from corporate governance in Israel -- About the editors -- Index.
Includes index.
Print version record
Keywords: International business enterprises; Corporate governance; Business & Economics -- General; Economics, finance, business & management